O-011 Symptomatic Intracranial Hemorrhage After Reperfusion Therapy – Impact of Definition on its Frequency. (29th July 2016) - von Kummer, R; Frei, D; Yoo, A; Zaidat, O; Khatri, P; Gupta, R; Lopes, D; Shownkeen, H; Meyer, D; Buell, H; Bach, V; Kuo, S; et al.
Abstract : Introduction: There is currently no standardized criterion for a clinically defined symptomatic intracranial hemorrhages (sICH), particularly secondary to endovascular therapy of ischemic stroke. Recent randomized controlled trials evaluating the efficacy and safety of intra-arterial therapy have published results with varying complication rates based upon the sICH definition employed. To further elucidate the variability in sICH outcome, the present study subjects the THERAPY cohort to definitions of sICH from similar trials. Materials and methods: The multicenter THERAPY trial enrolled a total of 108 patients randomized to either IV-tPA monotherapy or a combined thrombolytic and intra-arterial therapy. Angiography was performed at presentation and at 24 hours from intervention. To meet the present study criterion, patients included in the study must have the relevant data document for evaluation of sICH presence, defined in the THERAPY trial as 24 h CT evidence of an ECASS-defined intracranial hemorrhage and a worsening of ≥4 on the National Institute of Health Stroke Scale and compared to outcomes when subjecting the same cohort to definitions from related trials. Results: In total, 105 patients from the THERAPY trial met the criteria for analysis. Under the study definition (Definition A), the rate of sICH was observed to be 9.5% (10/105) for both arms of the THERAPY trial, with 9.3% (4/43) of patients documented for the combined therapy arm. More narrow definitions for sICH, such as those employed by REVASCAT and SWIFT PRIME, demonstrated a reduction in the rate for sICH of the THERAPY cohort to as low as 0.0% for the intervention arm (Table 1 ). Conclusion: Under the trial definition, any apparent extravascular blood in the brain or cranium with an increase of 4 or more on the NIHSS, associated or not, is considered a sICH; as a result, the inclusion of hemorrhagic infarctions (HI1 and HI2) in this definition resulted in an apparent relative increase in sICH rates. Subjecting the THERAPY cohort to other definitions yielded notable variance in complication rates. As there is no current standardization for the quantification of sICH, further analysis and data are needed to identify and standardize a succinct and relevant definition. Disclosures: R. von Kummer: 2; C; Penumbra, Inc. D. Frei: 3; C; Penumbra, Inc. A. Yoo: 1; C; National Institute of Health, Penumbra, Inc., Remedy Pharmaceuticals. O. Zaidat: 6; C; Penumbra, Inc. P. Khatri: 1; C; Penumbra, Inc. R. Gupta: 6; C; Penumbra, Inc. D. Lopes: 6; C; Penumbra, Inc. H. Shownkeen: None. D. Meyer: 5; C; Penumbra, Inc. H. Buell: 5; C; Penumbra, Inc. V. Bach: 5; C; Penumbra, Inc. S. Kuo: 5; C; Penumbra, Inc. A. Bose: 4; C; Penumbra, Inc. 5; C; Penumbra, Inc. S. Sit: 4; C; Penumbra, Inc. 5; C; Penumbra, Inc. J. Mocco: 1; C; Penumbra, Inc.